PO106 Alcohol abuse as a manifestation of obsessivity in huntington's disease. (1st December 2017) - Symonds, Alexander; Alusi, Sundus; Davies, Rhys
Abstract : Huntington's disease is an invariably fatal neurodegenerative disorder characterised by a triad of abnormal movement, progressive cognitive impairment and psychiatric or behavioural symptoms. This study looks at 53 patients from The Walton Centre EnrollHD database. In manifest patients, the most common presenting symptoms were psychiatric (n=17), followed by motor (n=13), cognitive (n=4) and mixed (n=2). Depression and bipolar disorder were common comorbidities (n=7, n=11). Of all patients, 29 drank over 14 units; two drank over 30 units a week. Two had a past medical history of alcohol abuse. Musculoskeletal comorbidities were more common in patients who abuse, or have abused alcohol (p<0.0001). The prevalence of psychiatric, cognitive and motor symptoms did not vary significantly with alcohol use. In addition, psychiatric symptoms did not occur earlier when drinking excessively (46 compared to 41 years old). Obsessivity, as measured by the Problem Behaviours Assessment, is on average higher in those that abuse alcohol versus those that do not drink (7.0 and 2.9 respectively). A one-tailed ANOVA indicated that this difference was not significant (p>0.05). The relationship between obsessivity and alcohol abuse is unclear in this small study sample, although it suggests a potential relationship between obsession and alcohol abuse.